Varietal Variances of Grain Nitrogen Content and Its Relations to Nitrogen Accumulation and Yield of High-Quality Rice under Different Nitrogen Rates - Jiale Wu; Renwei Que; Wenle Qi; Gangqiang Duan; Jingjing Wu; Yongjun Zeng; Xiaohua Pan; Xiaobing Xie (Agronomy, 2022)
Nitrogen (N) management is an important strategy for improving the yield, grain quality, and N use efficiency of rice (Oryza sativa). Exploring appropriate N application rates is essential for high-quality rice production in China, especially in the context of the large extension of these varieties in recent years. Field experiments were conducted to study changes of grain N content and their correlations to yield and yield components using twenty high-quality rice varieties grown at three N application rates (105, 165 and 225 kg ha−1) in 2019 and 2020. Additionally, a micro-plot experiment based on 15N isotope tracing technique was also conducted with two contrasting high-quality rice varieties of Y-liangyou 911 and Yeiangyoulisi under two N application rates (165 and 225 kg ha−1) in 2021, with grain N accumulation, its subdivision, and N utilization investigated. We found that the grain N content of high-quality rice increased with the increase of N application rates, while there was no consistent response in grain yield. There was a significant quadratic relationship between grain yield and grain N content, while panicles m−2 and grain-setting rate had a positive and a negative correlation with grain N content, respectively, in both 2019 and 2020. Across three N application rates and two years, the coefficient of variation (CV) of grain N content ranged from 10.36% to 21.26% among twenty varieties, of which Y-liangyou 911 had the smallest CV, and six varieties, including Yexiangyoulisi, had the largest CV. The micro-plot experiment showed that, in comparison with N165, the grain N content, grain N accumulation, and N recovery rate increased under N225 in both varieties, but a significant increase in grain yield was only observed for Y-liangyou 911. Grain N accumulation derived from panicle N fertilizer and its ratios to total grain N accumulation and the N recovery rate was significantly higher than those derived from basal and tillering N fertilizers. Nevertheless, increasing N application rates had much greater effects on the grain N accumulation derived from basal and tillering fertilizers and on ratios to total grain N accumulation in Yexiangyoulisi than those in Y-liangyou 911. Our results suggested that adopting a moderate N application rate (165 kg ha−1) is conducive to maintaining an appropriate grain N content and achieving higher grain yield and N use efficiency as well as better quality of high-quality rice. Besides, moderately reducing basal and/or tillering N fertilizers is necessary for those varieties with a larger CV of grain N content.